Criteria for selection and classification of studies in medical events - da Costa Vieira, René Aloisio [UNESP]; Paulinellli, Regis Resende; Rodrigues, Fábio Francisco Oliveira; Moreira, Marise Amaral Rebouças; Caponero, Ricardo; Pessoa, Eduardo Carvalho [UNESP]; Rahal, Rosemar Macedo Sousa; Facina, Gil; de Freitas Junior, Ruffo (FapUNIFESP (SciELO), 2023)
OBJECTIVE: The aim of this study was to evaluate the impact of study methodology and evaluation type on the selection of studies during the presentation of scientific events. METHODS: A prospective, observational, transversal approach was applied to a cohort of studies that were submitted for presentation at the 2021 Brazilian Breast Cancer Symposium. Three forms of criteria (CR) were presented. CR1 was based on six criteria (method, ethics, design, originality, promotion, and social contribution); CR2 graded the studies from 0 to 10 for each study, and CR3 was based on five criteria (presentation, method, originality, scientific knowledge, and social contribution). To evaluate the item correlation, Cronbach's alpha and factorial analysis were performed. For the evaluation of differences between the tests, we used the Kruskal-Wallis and post-hoc Dunn tests. To determine the differences in the study classifications, we used the Friedman test and Namenyi's all-pairs comparisons. RESULTS: A total of 122 studies were evaluated. There was also a good correlation with the items concerning criterion 1 (α=0.730) and 3 (α=0.937). Evaluating CR1 methodology, study design and social contribution (p=0.741) represents the main factor and CR3 methodology, and the scientific contribution (p=0.994) represents the main factor. The Kruskal-Wallis test showed differences in the results (p<0.001) for all the criteria that were used [CR1-CR2 (p<0.001), CR1-CR3 (p<0.001), and CR2-CR3 (p=0.004)]. The Friedman test showed differences in the ranking of the studies (p<0.001) for all studies (p<0.01). CONCLUSION: Methodologies that use multiple criteria show good correlation and should be taken into account when ranking the best studies.
Keywords: Congress; Meeting abstract; Methods; Planning techniques; Societies, scientific